Polymorphisms Associated with Age at Onset in Patients with Moderate-to-Severe Plaque Psoriasis - Rocío Prieto-Pérez; Guillermo Solano-López; Teresa Cabaleiro; Manuel Román; Dolores Ochoa; María Talegón; Ofelia Baniandrés; José Luis López-Estebaranz; Pablo de la Cueva; Esteban Daudén; Francisco Abad-Santos (Journal of Immunology Research)
Psoriasis is a chronic skin disease in which genetics play a major role. Although many genome-wide association studies have been performed in psoriasis, knowledge of the age at onset remains limited. Therefore, we analyzed 173 single-nucleotide polymorphisms in genes associated with psoriasis and other autoimmune diseases in patients with moderate-to-severe plaque psoriasis type I (early-onset, <40 years) or type II (late-onset, ≥40 years) and healthy controls. Moreover, we performed a comparison between patients with type I psoriasis and patients with type II psoriasis. Our comparison of a stratified population with type I psoriasis n=155 and healthy controls N=197 is the first to reveal a relationship between the CLMN, FBXL19, CCL4L, C17orf51, TYK2, IL13, SLC22A4, CDKAL1, and HLA-B/MICA genes. When we compared type I psoriasis with type II psoriasis N=36, we found a significant association between age at onset and the genes PSORS6, TNF-α, FCGR2A, TNFR1, CD226, HLA-C, TNFAIP3, and CCHCR1. Moreover, we replicated the association between rs12191877 (HLA-C) and type I psoriasis and between type I and type II psoriasis. Our findings highlight the role of genetics in age of onset of psoriasis.